2018
DOI: 10.1039/c8ta07901c
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional TcO4 sorption capacity and highly efficient ReO4 luminescence sensing by Zr4+ MOFs

Abstract: A Zr4+ MOF shows an exceptional capability to capture TcO4− and selective luminescence sensing for ReO4−, demonstrated for the first time for MOF materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 35 publications
3
46
0
Order By: Relevance
“…Theoretical calculation was carried out to further explore the structural information on ReO 4 – @PCN-993 via density functional theory calculations in the theoretical level of PBE/DNP using the DMol software (Figure S29). Consistent with the SCXRD studies, the Re1 anion binds to the framework via two amino groups, while Re2 is stabilized via C/O–H···O interactions, along with adsorption energies of −52.5 and −113.8 kcal/mol . Overall, the related results not only illustrate the detailed mechanism and efficient sorption sites of MOFs for ReO 4 – but validate the important CS feature of PCN-993.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…Theoretical calculation was carried out to further explore the structural information on ReO 4 – @PCN-993 via density functional theory calculations in the theoretical level of PBE/DNP using the DMol software (Figure S29). Consistent with the SCXRD studies, the Re1 anion binds to the framework via two amino groups, while Re2 is stabilized via C/O–H···O interactions, along with adsorption energies of −52.5 and −113.8 kcal/mol . Overall, the related results not only illustrate the detailed mechanism and efficient sorption sites of MOFs for ReO 4 – but validate the important CS feature of PCN-993.…”
supporting
confidence: 79%
“…Consistent with the SCXRD studies, the Re1 anion binds to the framework via two amino groups, while Re2 is stabilized via C/O−H•••O interactions, along with adsorption energies of −52.5 and −113.8 kcal/mol. 40 Overall, the related results not only illustrate the detailed mechanism and efficient sorption sites of MOFs for ReO 4 − but validate the important CS feature of PCN-993.…”
supporting
confidence: 55%
“…These recent findings open a very attractive avenue for MOF applications for environmental remediation of various contaminants (Mon et al, 2018) and nuclear waste treatment (Banerjee et al, 2016b;Dolgopolova et al, 2018). More recently, several MOFs (Banerjee et al, 2016a;Banerjee et al, 2016c;Drout et al, 2018;Fei et al, 2011;Li et al, 2017b;Mei et al, 2019;Rapti et al, 2018;Sheng et al, 2019;Sheng et al, 2017;Xu et al, 2019;Zhu et al, 2017a) and cationic organic framework (Da et al, 2019;Ding et al, 2020;He et al, 2019;Li et al, 2018;Liu and Han, 2020;Samanta et al, 2018;Shen et al, 2017;Sun et al, 2019;Zhu et al, 2017b) have demonstrated the ability to trap ReO 4 − from aqueous media.…”
Section: Introductionmentioning
confidence: 95%
“…Thus, it can be concluded that the ligand-to-ReO 4electron transfer will also be responsible for the observed fluorescence quenching. 30,32,55…”
Section: Crystalmentioning
confidence: 99%